ANALISIS NON PERFORMING LOAN DAN LOAN TO DEPOSIT RATIO PADA PT BANK PERKREDITAN RAKYAT BEPEDE KUTAI SEJAHTERA KAB. KUTAI KARTANEGARA PERIODE TAHUN 2014 – 2016 - Eka Pramelia; Dwi Risma Deviyanti; Dhina Mustika Sari (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
The purpose of this research is to know how of rural bank  BePeDe Kutai Sejahtera health in kutai kartanegara district be observed from non performing loan and loan to deposit ratio period 2014 to 2016. The research methods used in this research is to using non statistical analysis of quantitative data, by using banking financial ratio that is Non Performinga Loans Ratio and Loan to Deposit Ratio in 2014 to 2016, the ratio is calculated as a percentage by comparing the total non performing loans (substandard creadit,boubtfull credit and loss creadit) to total loans, and Loan to Deposit Ratio is calculated as a percentage by comparing the ratio of total loans to Third Party Funds (DPK) collected by the Bank. This ratio will show the level of ability of the Bank in channeling the funds coming from the community (in the form of: Current Account, Savings, Time Deposit, Time Deposit Certificate and Other Immediate Liabilities) in the form of Credit. Based on the results of the study can be concluded that the quality of NPL in 2014 to 2016 healthy because it is below the maximum threshold of 5% who have been dieting to form Bank Indonesia. For the quality of LDR 2014 to 2016 healthy because it is below the maximum limit of 94.75% despite being below the maximum limit but the maximum limit set by the PT BPR BePeDe Kutai Sejahtera. Some of the challenges and errors that have not been applied to SOP (Standard Operating Procedure) and have not yet had other standard rules and management are too numerous to provide credit for employees without any strong analysis. Keywords :  Analisis Credit, Non Performing Loan (NPL), Loan To Deposit Ratio (LDR), Bank Health Level.